2015
DOI: 10.4187/respcare.03779
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Safety of Endoscopic Ultrasound With Bronchoscope-Guided Fine-Needle Aspiration in Mediastinal Lymph Node Sampling: Systematic Review and Meta-Analysis

Abstract: BACKGROUND: The use of endoscopic ultrasound with bronchoscope-guided fine-needle aspiration (EUS-B-FNA) has been described in the evaluation of mediastinal lymphadenopathy. Herein, we conduct a meta-analysis to estimate the overall diagnostic yield and safety of EUS-B-FNA combined with endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), in the diagnosis of mediastinal lymphadenopathy. METHODS: The PubMed and EmBase databases were searched for studies reporting the outcomes of EUS-B-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 31 publications
11
78
0
4
Order By: Relevance
“…In combination with esophageal ultrasound-guided fine-needle aspiration (EUS-FNA ), it can provide more extensive mediastinal lymph node evaluation. A meta-analysis which evaluated EUS-B-FNA versus EUS-B-FNA plus EBUS-TBNA confirmed superiority of combination in lung cancer staging [13]. Analysis of 10 trials with 1080 subjects having mediastinal lymphadenomegaly showed sensitivity of the combined procedure significantly higher than EBUS-TBNA alone (91% vs. 80%, p = 0.004).…”
Section: Radial and Linear Endobronchial Ultrasound (Ebus)mentioning
confidence: 95%
“…In combination with esophageal ultrasound-guided fine-needle aspiration (EUS-FNA ), it can provide more extensive mediastinal lymph node evaluation. A meta-analysis which evaluated EUS-B-FNA versus EUS-B-FNA plus EBUS-TBNA confirmed superiority of combination in lung cancer staging [13]. Analysis of 10 trials with 1080 subjects having mediastinal lymphadenomegaly showed sensitivity of the combined procedure significantly higher than EBUS-TBNA alone (91% vs. 80%, p = 0.004).…”
Section: Radial and Linear Endobronchial Ultrasound (Ebus)mentioning
confidence: 95%
“…However, EBUS bronchoscope has been also used to perform transesophageal needle aspiration and the technique is called as Endoscopic ultrasound (with bronchoscope)-guided fine needle aspiration (EUS-B-FNA) in some centres. Where such expertise exists mediastinal masses could potentially be approached in same sitting via both transbronchial and transesophageal routes and this may increase diagnostic yield [18]. Experience with EUS-B-FNA was limited and was not routine practice in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound guided FNA (through the esophagus) can increase access to left paratracheal, inferior mediastinum, and aortopulmonary window nodes. When added to EBUS-TBNA, it can increase the ability to diagnose lymphadenopathy by 7.6% (37).…”
Section: Ebusmentioning
confidence: 99%